Risk Prediction Model for Heart Failure and Cardiomyopathy After Adjuvant Trastuzumab Therapy for Breast Cancer. Issue 1 (28th February 2014) - Ezaz, Ghideon; Long, Jessica B.; Gross, Cary P.; Chen, Jersey
Abstract : Background: Adjuvant trastuzumab improves survival for women with human epidermal growth factor receptor 2‐positive breast cancer, but increases risk for heart failure (HF) and cardiomyopathy (CM). However, clinical trials may underestimate HF/CM risk because they enroll younger subjects with fewer cardiac risk factors. We sought to develop a clinical risk score that identifies older women with breast cancer who are at higher risk of HF or CM after trastuzumab. Methods and Results: Using the Surveillance, Epidemiology and End Results (SEER)‐Medicare database, we identified women with breast cancer who received adjuvant trastuzumab. Using a split‐sample design, we used a proportional hazards model to identify candidate predictors of HF/CM in a derivation cohort. A risk score was constructed using regression coefficients, and HF/CM rates were calculated in the validation cohort. The sample consisted of 1664 older women (mean age 73.6 years) with 3‐year HF/CM rate of 19.1%. A risk score consisting of age, adjuvant chemotherapy, coronary artery disease, atrial fibrillation or flutter, diabetes mellitus, hypertension, and renal failure was able to classify HF/CM risk into low (0 to 3 points), medium (4 to 5 points), and high (≥6 points) risk strata with 3‐year rates of 16.2%, 26.0%, and 39.5%, respectively. Conclusions: A 7‐factor risk score was able to stratify 3‐year risk of HF/CM after trastuzumab between the lowest and highest risk groups by more than 2‐fold in a Medicare population. These findings will inform future research aimed at further developing a clinical risk score for HF/CM for breast cancer patients of all ages.